Toxicological effects of fipronil on the midgut and brain of the stingless bee Partamona helleri Friese (Hymenoptera: Apidae) - Gomes, Cliver Fernandes Farder (2021)
Partamona helleri Friese is a stingless bee that pollinates native and cultivated plants in Brazil. The general decline of the bee population has been associated with many factors, including exposure to insecticides. Among insecticides used in agriculture and forestry in Brazil, fipronil is particularly important due to its toxicity to non-target organisms, including bees. In this context, this study aimed to evaluate the side effects of fipronil LC 50 on the midgut and brain of P. helleri workers after oral exposure. In chapter 1, the fipronil effects on the midgut morphology, antioxidant activity, and some pathways of cell death, cell proliferation and differentiation in the workers were evaluated. Fipronil caused disorganization of the midgut epithelium and increased the activities of the detoxification enzymes superoxide dismutase, catalase and glutathione S-transferase. In addition, there was an increase in the signaling-pathway proteins caspase-3, peroxidase, and ERK 1/2 in the midgut of exposed bees, but a decrease in the proteins JNK, Wg, Armadillo, Notch, and Prospero, indicating the induction of cell death and impairment of the midgut epithelial renewal. In chapter 2, the effects of fipronil on the behavior, brain morphology, antioxidant activity, and proteins related to cell signaling pathways on workers' brains were evaluated. The insecticide ingestion caused hyperactivity in the bees and damaged the brain. Fipronil also decreased the activity of catalase but increased the activity of glutathione S-transferase. Furthermore, exposed bees showed an increase in the number of positive cells for caspase-3 and peroxidase but a reduction in positive cells for ERK 1/2, JNK, and Notch, suggesting neuron death and impaired brain function. Together, these results demonstrate that fipronil significantly affects the morphology and physiology of two important organs of the stingless bee P. helleri, which may threaten the individuals and colonies of this important Neotropical pollinator. Keywords: Pollinator. Midgut. Brain. Fipronil. Signaling pathways.